Feasibility of nasal bridge pressure injury prevention using a protective dressing and the Halyard Fluidshield® N95 mask in a COVID‐positive environment. Issue 2 (18th July 2022) - Holder, Hazel; Aningalan, Alexis M.; Walker, Stephanie; Cato, Kenrick; Gannon, Brittany "Ray"
Abstract: The purpose of this study was to prevent nasal bridge pressure injury among fit‐tested employees, secondary to long‐term wear of the N95 mask during working hours. A prospective, single‐blinded, experimental cohort design. Participants were enrolled using the convenience sampling methods and randomisation was utilised for group assignment. Eligibility was determined by a COVID Anxiety Scale score and non‐COVID clinical assignment. Participants with a history of previous skin injury or related condition were excluded. The experimental group was assigned Mepilex Lite® and the control group used Band‐ Aid®. Formal skin evaluations were done by Nurse Specialists who are certified in wound and ostomy care by the Wound, Ostomy, Continence, Nursing Certification Board (WOCNCB®). Fit test logs were provided to participants to measure subjective user feedback regarding mask fit and level of comfort. The results of this feasibility trial are promising in supporting the use of a thin polyurethane foam dressing as a safe and effective dressing to apply beneath the N95 mask. Additional research is needed to validate results due to limited data on efficacy and safety of the various barrier dressings as a potential intervention to prevent skin breakdown to the nasal bridge.